Current research on respiratory viral infections: XIII International Symposium on Respiratory Viral Infections: part 1. (October 2011) - Welkers, Matthijs RA; Sutherland, Tom; Osterhaus, Albert DME; Monto, Arnold; de Jong, Menno D; Hayden, Frederick G
The XIII International Symposium on Respiratory Viral Infections was convened by The Macrae Group LLC (NY, USA) in Rome, Italy, on the 13–16 March 2011. This annual symposium provides a forum for public health specialists, vaccinologists, clinicians, virologists and pharmacologists to discuss recent advances in respiratory virus research in an interdisciplinary fashion. Here, we highlight presentations at this conference with a special focus on influenza.